Clusters As Vehicles Stimulating Regional and Local Development - Ewa Bojar (European Regional Science Association (ERSA), 2006)
Past experience of European Union member states acknowledge significant role of regions in the process of European integration. As a matter of fact regions compete for capital but what should be simultaneously highlighted they also collaborate in many fields. To a large extent regional and local development is determined by clusters, which are groups of complementary enterprises having certain similarities with one another as well as linked institutions engaged in a certain area. Clusters can play crucial role in improving competitiveness and stimulate innovation in regions, especially those economically backward as well as in Polish economy as a whole. The aim of this paper is to survey some theoretical concepts and practical aspects of functioning clusters, especially good practices and shortcomings in the context of regional and local development, and presentation of Polish relevant experiences and expectations. This paper presents a few clusters operating in Poland, with special focus on two clusters run in underdeveloped Lublin region – Ecological Food Valley and Aviation Valley.
Keywords: 330